Natural kinds - Khalidi, Muhammad Ali (Professor of philosophy) (Cambridge elements. Elements in the philosophy of science, 2023)
Scientists cannot devise theories, construct models, propose explanations, make predictions, or even carry out observations, without first classifying their subject matter. The goal of scientific taxonomy is to come up with classification schemes that conform to nature's own. Another way of putting this is that science aims to devise categories that correspond to 'natural kinds'. The interest in ascertaining the real kinds of things in nature is as old as philosophy itself, but it takes on a different guise when one adopts a naturalist stance in philosophy, that is when one looks closely at scientific practice and takes it as a guide for identifying natural kinds and investigating their general features. This Element surveys existing philosophical accounts of natural kinds, defends a naturalist alternative, and applies it to case studies in a diverse set of sciences.